THE EFFECT OF PROFITABILITY, COMPANY AGE, AND PUBLIC OWNERSHIP ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Anita Gunawan; Hardian Rahmat Puntoro; Rinaldy Putra Pakolo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The objective of this study is to prove the effect of profitability, company age, and public ownership on the disclosure of Corporate Social Responsibility in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015 and 2017 in 120 companies. The data used in this research is secondary data; the sample is analyzed using Multiple Linear Regression Analysis. The results conclude that the profitability has a positive effect on disclosure of corporate social responsibility reports, while company age and public share ownership does not significantly affect the disclosure of corporate social responsibility reports.